2018
DOI: 10.4103/jhrs.jhrs_65_17
|View full text |Cite
|
Sign up to set email alerts
|

Live birth after rescue in vitro maturation–intracytoplasmic sperm injection in type 1 diabetes, polycystic ovary syndrome patient using clomiphene–antagonist protocol

Abstract: Infertility in patients with polycystic ovary syndrome (PCOS) associated with diabetes leads to challenging situations seeking alternative treatments. In vitro maturation (IVM) followed by intracytoplasmic sperm injection (ICSI) could overcome the challenges with promising pregnancies in such patients. In the treatment of a 32-year-old diabetic woman who also had PCOS, single immature oocyte was retrieved. Rescue IVM followed by ICSI yielded a grade 1 day 3 embryo which on transferring resulted in pregnancy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In addition, no significant effects of clinical factors on the maturation rate within 24 h were observed. Taken together, immature oocytes collected from routine COH cycles still have a great potential to reach maturation by in vitro culture, regardless of the clinical characteristics, ovarian stimulation protocol, and oocyte diameter, confirming the necessity and prospect of the R-IVM [ 3 , 16 21 ].…”
Section: Discussionmentioning
confidence: 93%
“…In addition, no significant effects of clinical factors on the maturation rate within 24 h were observed. Taken together, immature oocytes collected from routine COH cycles still have a great potential to reach maturation by in vitro culture, regardless of the clinical characteristics, ovarian stimulation protocol, and oocyte diameter, confirming the necessity and prospect of the R-IVM [ 3 , 16 21 ].…”
Section: Discussionmentioning
confidence: 93%
“…We observed that in reproductive aging, mRNA GC content was associated with longer half-life and increased translational output. Although the RNA-seq data used in our analysis was from IVF patients whose GV oocytes failed to mature following hCG administration and were then rescued with in vitro maturation (Reyes et al 2017; Virant-Klun et al 2016), rescue in vitro maturation can result in pregnancies and live births (Lee et al 2016; Elanchezhian et al 2018). In the future it will be highly valuable to assess human reproductive aging in oocytes from healthy individuals in order to identify molecular signatures of advanced maternal age.…”
Section: Resultsmentioning
confidence: 99%
“…The exploration of treatment strategies for infertility of the patients with PCOS associated with diabetes is extremely significant for these females. The combination of IVM and intracytoplasmic sperm injection (ICSI) provided an effective method to overcome the challenges of infertility treatment in patients with PCOS associated with diabetes [ 11 ]. Therefore, IVM may be a promising method to avoid high glucose caused damage to oocytes and to provide oocytes for ART of patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%